SURVEY OF PRESCRIPTION PATTERN OF ANTIHYPERTENSIVE DRUGS IN HYPERTENSIVE AND DIABETIC HYPERTENSIVE PATIENTS - Panda, Bipin B; Pati, Manas R; Sahu, Pratap K (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Objective: This study was conducted in order to establish the drug prescribing trend of anti-hypertensive agents in hypertensives and diabetic hypertensives in General Medicine Department of Veer Surendra Sai Medical College and Hospital, Sambalpur, Odisha. Methods: A prospective study of 2 months duration was conducted at the Veer Surendra Sai Medical College and Hospital, Sambalpur. The prescriptions containing antihypertensives were collected from the patients attending the outpatient department of general medicine. Pregnant women were excluded from the study. Results: A total of 422 prescriptions were monitored, of which 285 were male and 137 were female. The age group of the patients varies from 35 to 75 years. Among 422 prescriptions, 118 prescriptions were of hypertensives and 304 prescriptions were diabetic hypertensives. Among hypertensives, 48% of patients were treated with anti-hypertensive drug combinations and 52% of patients were treated with single anti-hypertensive drug. 83% patients are suffering from primary hypertension (HTN) and only 17% patients suffering from secondary HTN. For the treatment of HTN, both monotherapy and combination therapy were followed. In monotherapy, amlodipine was most commonly prescribed followed by telmisartan. In combination therapy, a two-drug combination consisting of calcium channel blockers (amlodipine) and beta blocker (atenolol) were given to the majority of patients, followed by amlodipine and AT1 antagonist (telmisartan or olmesartan) combination. Among diabetic hypertensives, 31% of patients were treated with single anti-hypertensive drug and 69% of patients were treated with anti-hypertensive drug combinations. In monotherapy, beta-blocker (metoprolol) was most commonly prescribed. In combination therapy, a two-drug combination consisting of calcium channel blockers (amlodipine) and beta blocker (atenolol or metoprolol) were given to the majority of patients, followed by a combination of calcium channel blockers (amlodipine) and AT1 antagonist (telmisartan or olmesartan). Conclusion: The present study represents the current prescribing trend for anti-hypertensive agents. According to JNC 7 guidelines, for Stage 1 HTN (systolic blood pressure [SBP] 140-159 or diastolic blood pressure [DBP] 90-99 mmHg), thiazides-type diuretics should be prescribed. For Stage 2 HTN (SBP ≥160 or DBP ≥100 mmHg), two drug combinations (usually thiazide-type diuretics and angiotensin converting enzyme inhibitors) should be prescribed. In our study, the prescription pattern does not follow the guideline. Keywords: Hypertension, Prescription, Diabetes, Cardiovascular disease.